Pendampingan Pemasaran Langsung Online Hasil Pertanian Sayuran Segar di Kecamatan Lingsar - Tajidan Tajidan; Arifuddin Sahidu; Suparmin Suparmin; Halil Halil (Jurnal Gema Ngabdi, 2022)
Income risk borne by farming households is a crucial issue. These problems are overcome by carrying out community service activities. The purpose of community service activities is so that farmer households are able to do direct marketing to consumers, are able to use cellphones as promotional media and communicate directly with customers. This goal is achieved through an adult education approach. The adult education approach is carried out using guidance and training methods for millennial farmer households and/or sons and daughters of farmers to conduct direct marketing and promotion to consumers. The results of community service show that half of the participants have used e-commerce in making sales, and only one of the 16 participants has used WhatsApp as a medium for direct online marketing promotion of fresh vegetable farms.